Tinjauan Yuridis dalam Pemeriksaan Sidik Jari Dalam Penyidikan Tindak Pidana di Polres Pulau Buru - Lutfi Rumkel (Sanskara Hukum dan HAM, 2022)
The principle of legal awareness means making every citizen aware to always obey the law, besides that it is also obligatory for the state and its apparatus to enforce and guarantee the validity of legal certainty in Indonesia.  With  the  increasingly  advanced  and  complex  era  and changes that occur in all directions, indirectly bring up various things in life. Along with the increasing phenomenon of legal problems, there is  also  an  increase  in  juridical  studies  that  aim  to  explore  various problems from the perspective of existing laws and regulations. In such a situation and condition, it is hoped that the crimes that occurred can be considered more seriously, both for the competent authorities and for the participation of the community, which operationally have not been satisfactorily resolved. The imposition of a crime is not merely as revenge  but  is  aimed  at  influencing  human  behavior  in  accordance with the rules of law.